MicroRNA-155 influences B-cell receptor signaling and associates with aggressive disease in chronic lymphocytic leukemia - Cui, Bing; Chen, Liguang; Zhang, Suping; Mraz, Marek; Fecteau, Jessie-F; Yu, Jian; Ghia, Emanuela M; Zhang, Ling; Bao, Lei; Rassenti, Laura Z; Messer, Karen; Calin, George A; et al. (Blood, 2014)
High-level leukemia cell expression of micro-RNA 155 (miR-155) is associated with more aggressive disease in patients with chronic lymphocytic leukemia (CLL), including those cases with a low-level expression of ζ-chain-associated protein of 70 kD. CLL with high-level miR-155 expressed lower levels of Src homology-2 domain-containing inositol 5-phosphatase 1 and were more responsive to B-cell receptor (BCR) ligation than CLL with low-level miR-155. Transfection with miR-155 enhanced responsiveness to BCR ligation, whereas transfection with a miR-155 inhibitor had the opposite effect. CLL in lymphoid tissue expressed higher levels of miR155HG than CLL in the blood of the same patient. Also, isolated CD5(bright)CXCR4(dim) cells, representing CLL that had been newly released from the microenvironment, expressed higher levels of miR-155 and were more responsive to BCR ligation than isolated CD5(dim)CXCR4(bright) cells of the same patient. Treatment of CLL or normal B cells with CD40-ligand or B-cell-activating factor upregulated miR-155 and enhanced sensitivity to BCR ligation, effects that could be blocked by inhibitors to miR-155. This study demonstrates that the sensitivity to BCR ligation can be enhanced by high-level expression of miR-155, which in turn can be induced by crosstalk within the tissue microenvironment, potentially contributing to its association with adverse clinical outcome in patients with CLL.
Keywords: dospělí; CD5 Antigens; inositolpolyfosfát-5-fosfatasy; Female; Blotting, Western; průtoková cytometrie; Adult; ženské pohlaví; Leukemia, Lymphocytic, Chronic, B-Cell; fosfatasy; nádorové mikroprostředí; Receptors, CXCR4; lidé; Flow Cytometry; receptory CXCR4; messenger RNA; antigeny CD5; polymerázová řetězová reakce s reverzní transkripcí; signální transdukce; vápník; míra přežití; Aged, 80 and over; Signal Transduction; prognóza; regulace genové exprese u leukemie; RNA, Messenger; Receptors, Antigen, B-Cell; western blotting; protein-tyrosinkináza ZAP-70; Calcium; Male; nádorové biomarkery; Aged; ligand CD40; Reverse Transcriptase Polymerase Chain Reaction; mikro RNA; ZAP-70 Protein-Tyrosine Kinase; Prognosis; Survival Rate; Gene Expression Regulation, Leukemic; receptory antigenů B-buněk; Biomarkers, Tumor; lidé středního věku; MicroRNAs; senioři nad 80 let; Tumor Microenvironment; senioři; mužské pohlaví; Phosphoric Monoester Hydrolases; Inositol Polyphosphate 5-Phosphatases; Middle Aged; kvantitativní polymerázová řetězová reakce; chronická lymfatická leukemie; CD40 Ligand; Real-Time Polymerase Chain Reaction; Humans